MAQASHID SHARIA AS A FRAMEWORK OF ETHICS FOR ECONOMIC DOWNSTREAMING POLICY TOWARD INDONESIA GOLD 2045 - M. Zikwan (IZZI: Jurnal Ekonomi Islam, 2026)
Indonesia Emas 2045 is an ambitious vision that aims to make Indonesia a developed country with a strong, inclusive, and sustainable economy. To achieve this vision, the country needs economic transformation based on the principles of justice and sustainability. However, the implementation of downstreaming still faces structural dilemmas in the form of unequal distribution of benefits, dependence on foreign investment, and ecological pressures caused by resource exploitation. Through a qualitative-descriptive approach, this study explores the correlation between the principles of maqashid sharia and economic downstreaming policies, and provides strategic recommendations for policymakers to ensure an inclusive direction for economic development. This study argues that the application of maqashid sharia principles in economic downstreaming policies can support the Indonesia Emas 2045 vision by creating a fair, inclusive, and sustainable economy. Hifz al-Maal emphasizes the optimization of natural resource added value with fair distribution of benefits, reducing dependence on foreign investment. Hifz an-Nafs focuses on creating decent jobs and protecting workers. Hifz al-Aql encourages technology transfer and human capacity development, strengthening global competitiveness. Hifz an-Nasl ensures environmental sustainability through responsible resource exploitation. Hifz ad-Din guarantees ethical principles in economic development, avoiding exploitative practices. This study confirms that the implementation of maqashid syariah can overcome the dilemma between short-term economic interests and long-term sustainability, ensuring social justice, environmental sustainability, and community welfare. In conclusion, maqashid syariah is a relevant ethical framework for directing Indonesia's economic downstreaming towards an inclusive and sustainable economy.